2019
DOI: 10.1111/ner.12930
|View full text |Cite
|
Sign up to set email alerts
|

An Acute Randomized Controlled Trial of Noninvasive Peripheral Nerve Stimulation in Essential Tremor

Abstract: Objective To evaluate the safety and effectiveness of a wrist‐worn peripheral nerve stimulation device in patients with essential tremor (ET) in a single in‐office session. Methods This was a randomized controlled study of 77 ET patients who received either treatment stimulation (N = 40) or sham stimulation (N = 37) on the wrist of the hand with more severe tremor. Tremor was evaluated before and immediately after the end of a single 40‐minute stimulation session. The primary endpoint compared spiral drawing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(104 citation statements)
references
References 43 publications
5
92
0
7
Order By: Relevance
“…In fact, Tass et al [29] showed in Parkinsonian monkeys that coordinated reset neuromodulation of the subthalamic nucleus had more pronounced after-effects than classical neuromodulation with DBS-like (high) intensity. Pahwa et al [11] have also suggested that modulation of afferent pathways may produce an effect in supraspinal centers such as the Ventral Intermediate Nucleus (VIM), which is a brain target for DBS or HIFU for tremor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Tass et al [29] showed in Parkinsonian monkeys that coordinated reset neuromodulation of the subthalamic nucleus had more pronounced after-effects than classical neuromodulation with DBS-like (high) intensity. Pahwa et al [11] have also suggested that modulation of afferent pathways may produce an effect in supraspinal centers such as the Ventral Intermediate Nucleus (VIM), which is a brain target for DBS or HIFU for tremor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that stimulation of afferent nerve fibers below motor threshold (below MT) may also modulate tremor without the main drawbacks of stimulation above MT [7], [9]. For instance, a wrist-worn peripheral nerve stimulator showed its potential to reduce tremor right after stimulation compared to sham [10], [11]. Another study tested stimulation below MT of several upper limb muscles and reported reduction of wrist tremor during stimulation and also 5 minutes following the end of stimulation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Another non-invasive form of treatment is the handheld assistive device using active cancellation of tremor technology, which has shown some promise in reducing tremor amplitude and severity while performing tasks in a limited pilot trial 121. Efficacy of non-invasive peripheral nerve stimulation was assessed in a randomised controlled study by Pahwa et al 122. Subjects receiving a single in-office session of peripheral nerve stimulation showed transient relief in hand tremor symptoms.…”
Section: Non-invasive Therapies For Etmentioning
confidence: 99%
“…This research (with the same device) was followed with a pivotal study, where it was shown that subjects who received peripheral nerve stimulation did not show a significantly larger improvement in the Archimedes spiral task compared to sham but did show a significantly greater improvement in upper limb TETRAS tremor scores ( p = 0.017) compared to sham. No significant adverse events were reported; 3% of subjects experienced mild adverse events [ 24 ]. Vibrating Gaussian noise emitting manipulandum has been shown to improve motor performance.…”
Section: Discussionmentioning
confidence: 99%
“…We did not identify major safety risks during the clinical study; however, the local hand arm vibration is associated with the development of certain conditions: Raynaud’s phenomenon, carpal tunnel syndrome [ 28 ], vibration-induced white finger disease [ 29 ], finger pain, back pain, muscular pain or fatigue [ 30 ], chronic subdural hematoma (local application to the head) [ 31 ], skin irritation (including redness, itchiness, and/or swelling) [ 24 ], finger blood flow reduction [ 30 , 31 , 32 , 33 ], and neck and upper limb musculoskeletal disorders. Vibration can increase the postural and rest tremor [ 34 ], exacerbate Dupuytren’s contracture, and have various osteoarticular effects (hand and carpal bone vacuoles and cysts, Kienbock’s disease, navicular pseudoarthrosis, olecranon spurs, and osteoarthrosis of the wrist and elbow joints).…”
Section: Discussionmentioning
confidence: 99%